Intercostal nerve conduction and posterior rhizotomy in the diagnosis and treatment of thoracic radiculopathy - Johnson, E. Ralph (1974)
Intercostal nerve conduction study has proved to be an accurate technique in diagnosis of thoracic radiculopathy in 161 patients, 80 of whom had subsequent posterior rhizotomy with relief of pain in 81% of those undergoing surgery. The only significant complication of intercostal nerve conduction study is an 8·8% incidence of pneumothorax.